Rehabilitation of mentally retarded children - Shukla TR (Journal of All India Institute of Speech and Hearing, 1972)
Mentally Retarded are those unfortunate persons, whose mental growth isarrested or incomplete. These individuals have been posing problems to society invarious ways and society has been trying to help them in order to help itself. Muchhas been done for them in advanced countries, but very little has been done in India.There are many aspects of the problem such as classification, causes, prevention andtreatment, etc.